A new species of Stenus (Hemistenus) with new records and a key to Chinese species of the viridanus group (Coleoptera, Staphylinidae) - Zhao, Cai-Yun; Zhou, Hong-Zhang (Zootaxa, 2006)
Stenus (Hemistenus) uncinulatus Zhao & Zhou, sp. n. is described from Sichuan, China. Stenus (H.) guenai Rougemont is recorded from China for the first time. For some species new records and illustrations of spermatheca are presented. A revised key to the Chinese species of the viridanus group is provided.